1997
DOI: 10.1097/00005176-199701000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Quantitative Determination of Pancreatic Elastase 1 in Feces of Children

Abstract: Fecal E1 concentration appears to be a more sensitive and specific test of pancreatic function than other tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 5 publications
3
40
0
6
Order By: Relevance
“…It is stable, unaffected by exogenous pancreatic enzyme treatment, and correlates well with stimulated pancreatic function tests. [27][28][29] There may be some transient mild pancreatic insufficiency associated with some reduction in EL1 levels in patients with celiac disease before treatment. This is not to the same degree as the pancreatic insufficiency associated with cystic fibrosis.…”
Section: Identification Of a Pancreatic Lesionmentioning
confidence: 99%
“…It is stable, unaffected by exogenous pancreatic enzyme treatment, and correlates well with stimulated pancreatic function tests. [27][28][29] There may be some transient mild pancreatic insufficiency associated with some reduction in EL1 levels in patients with celiac disease before treatment. This is not to the same degree as the pancreatic insufficiency associated with cystic fibrosis.…”
Section: Identification Of a Pancreatic Lesionmentioning
confidence: 99%
“…6 -8 More recently, fecal E1 test has been demonstrated to have very good sensitivity in PI CF patients. 11,[25][26][27] Yet, in milder forms of CF pancreatic insufficiency, the sensitivity of the test was reduced. 24,27 Therefore, one could expect a higher sensitivity and specificity of fecal E1 test.…”
Section: Fecalmentioning
confidence: 99%
“…Previous studies reported a satisfying sensitivity around 100% for severe EPI [8][9][10]15] . However, its sensitivity in detecting mild forms of EPI was only 22-65% [9,15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of fecal elastase 1 (FE1) concentration is relatively simple and noninvasive. It has been reported to be a sensitive screening test for severe EPI [8][9][10] . In addition, the adult reference value for FE1 of greater than 200 g/g feces can be applied to infants older than 2 weeks [11] .…”
Section: Introductionmentioning
confidence: 99%